Ontario Healthcare Coverage Eligibility Among New Permanent Residents: A Scoping Review. Issue 4 (2nd October 2017) - Bobadilla, Andrea; Orchard, Treena; Magalhães, Lilian; Fitzsimmons, Deborah
ABSTRACT: New permanent residents to Ontario can experience difficulties accessing health services due to the 3-month residency requirement for provincial healthcare coverage. This scoping literature review, which included peer-reviewed articles and gray literature from 1993–2013, examined the effects of the 3-month waiting period on the health of new permanent residents to Ontario, public health, and the health-care system. At the individual level, issues of affordability, pre-existing conditions, and quality of care were prominent throughout the literature. At a systems level, the policy was found to constrain various health-care settings, pose a risk to public health, and compound health-care system costs.